Suitability of West African gramineous stemborers for the development of Cotesia species - Hailemichael, Y.; Schulthess, F.; Smith, W.; Overholt, W.A. (Springer, 1997)
The palaeotropical, gregarious, endoparasitic braconids Cotesia sesamiae, Cotesia flavipes and Cotesia chilonis were recently imported into Benin as candidates for biological control of stem and cob borers of maize. Host acceptability and host suitability of six gramineous borers occurring in western Africa, namely the noctuids Sesamia calamistis, Sesamia poephaga, Busseola fusca and the pyralids Coniesta ignefusalis, Eldana saccharina andMussidia nigrivenella, to these candidate parasitoids was evaluated in order to gain insight into the physiological suitability of the natural and factitious hosts. All hosts were accepted by all Cotesia spp., except M. nigrivenella which was not attacked by Co. chilonis. Parasitoid progeny development was successful in S. calamistis, S. poephagaand Con. ignefusalis. Sesamia calamistis was the most suitable host for Cotesia spp. development, in terms of duration of developmental time, brood size and mortality of parasitoid progeny.